Óleos essenciais e compostos fenólicos de espécimes masculinos e femininos de Baccharis uncinella DC - Jasinski, Vanesssa Cristina Godoy (2010)
This study aimed to: develop methodological sequences for the collection and analysis of essential oils and phenolic compounds of B. uncinella, applicable to the study of other species of the genus Baccharis; determined by techniques of gas chromatography-mass spectrometry, the chemical composition of essential oils from the leaves of male and female specimens of B. uncinella from different populations of the plant growing in nature; isolate and determine the chemical structure of phenolic compounds present in leaves using mainly chromatographic and spectroscopic methods. In the Campos Gerais of Paraná, it was observed the occurrence of two supposed varieties of B. uncinella, Bu1 and Bu2, with markedly different sizes and quite different flowering times. For the first time the leaves were collected from male and female specimens of two populations of B. uncinella, proceed to the extraction and analysis of essential oils by GC-MS techniques. The essential oils of four samples had very similar compositions, as opposed to frequently published data indicating no difference between the compositions of oils of male and female specimens of the same species of Baccharis. The results obtained in this study are due to the care in collections of male and female specimens (in the same place and time), in the preparation of material (careful separation of the leaves), using the same conditions in the hydrodestillation and analysis by CG-EM . All four samples had low levels of monoterpenes and the following sesquiterpenes as the main components: caryophyllene (Bu1 10.03% and Bu1 7.64%; Bu2 6.06% and Bu2 7.96%); spathulenol (Bu1 28.99% and Bu1 29.68%; Bu2 24.30% and Bu2 16.94%), caryophyllene oxide (Bu1 12.98% and Bu2 14.24%; Bu2 9.75% and Bu2 23.52%). These results also confirmed the botanical identifications that were made based on the morphology of flowers, indicating the inexistence of the supposed sub-species. The water remaining after the hydrodestillation was extracted with CHCl3 and then with AcOEt, yielding four extracts containing mainly 3.5-dicaffeoylquinic and 3.4-dicaffeoylquinic acids, as demonstrated by analysis of their 1H and 13C NMR spectra. The leaves were also extracted in Sohxlet using three solvents in sequence: CHCl3, AcOEt and MeOH. Part of the methanol extract was purified by dissolving it in water, removing the precipitates formed by a cold rest and extracting it with AcOEt. The extract thus obtained with ethyl acetate was subjected to several vacuum chromatography steps leading to the isolation and identification of 3,5- dicaffeoylquinic acid by the analysis of its 1H and 13C NMR spectra. This route to the phenolic compounds was improved by obtaining extracts with ethyl acetate from aqueous solution at pH 8 and pH 3. The extract made in slightly alkaline conditions contained mainly flavonoids, while the one obtained at pH 3 contained derivatives of quinic acid. The AcOEt extract at pH 8 was fractionated on silica gel column under pressure leading to the isolation of three flavonoids identified by their UV, 1H and 13C NMR spectra (quercetin, luteolin and apigenin). The AcOEt extract at pH 4 was fractionated on a silica gel column leading to the isolation and identification of 3,4-dicaffeoylquinic acid by the 1H and 13C NMR spectra.